Free Trade Agreements and the Movement of Business People - Thierry Mayer; Hillel Rapoport; Camilo Umana-Dajud (Institute of Labor Economics (IZA), 2024)
Using provisions to ease the movement of business visitors in trade agreements, we show that removing barriers to the movement of business people promotes trade. We document the increasing complexity of Free Trade Agreements and develop an algorithm that combines machine learning and text analysis techniques to examine the content of FTAs. We use the algorithm to determine which FTAs include provisions to facilitate the movement of business people and whether these are included in dispute settlement mechanisms. We show that provisions facilitating business travel are effective in promoting them and eventually increase bilateral trade flows.
Keywords: F13; F22; F23; 330; text analysis; machine learning; free trade agreements; business travel; migration